DIALOG MORAL UNIVERSAL HARMONISASI PEMIKIRAN HABERMAS, AL-FARABI, DAN KONFUSIUS DALAM ETIKA KOMUNIKASI LINTAS BUDAYA - Bustami, Bustami; Zulkarnain, Iskandar; Mailin, Mailin (STIT Ibnu Rusyd Tanah Grogot, 2025)
This research aims to develop the concept of universal moral dialogue by harmonizing the thoughts of three important figures: Jürgen Habermas, Al-Farabi, and Confucius in the context of the ethics of intercultural communication. Habermas put forward a theory of communicative action that emphasizes rationality and intersubjective agreement. Meanwhile, Al-Farabi highlighted the importance of virtue and collective purpose in creating an ideal society, and Confucius emphasized the principles of harmony, hierarchical relationships, and the values of politeness. Through qualitative analysis with a literature study approach, this study finds similarities between the three thoughts, namely the importance of a dialogue based on morality that integrates rationality, virtue, and harmony. The proposed model of intercultural communication consists of five main pillars: equality in dialogue, respect for diversity, the search for common truth, the application of virtue, and the achievement of collective harmony. This model is particularly relevant in facing the increasingly urgent challenges of globalization for ethical and inclusive intercultural interactions.